Direct Training to Increase Agreement Between Teachers' and Observers' Treatment Integrity Ratings. (September 2018) - Fallon, Lindsay M.; Sanetti, Lisa M. H.; Chafouleas, Sandra M.; Faggella-Luby, Michael N.; Briesch, Amy M.
To evaluate students' responsiveness to an intervention, both student outcome and implementer treatment integrity data are needed. Teachers are often asked to self-report treatment integrity data. However, when self-report responses are compared with those from a direct observer, it is apparent that teachers commonly overestimate the extent to which an intervention was implemented as planned. As such, more research related to teacher self-report to assess treatment integrity is needed. The objective of this preliminary single-case multiple-baseline design study was to improve interrater agreement between observers' and teachers' self-report ratings of treatment integrity by providing teachers with comprehensive, direct training (including an intervention description, modeling, practice, and feedback). Results indicate that after this training, agreement between observers' and teachers' ratings of treatment integrity improved.